The Contribution and Therapeutic Potential of Epigenetic Modifications in Alzheimer’s Disease - Wood, Ian C. (Frontiers in Neuroscience, 2018)
Alzheimer’s disease is a progressive neurodegenerative disorder, affecting 50 million people worldwide, for which there is no cure or effective treatment. Individuals suffering from Alzheimer’s show a decline in cognition over time beginning with memory loss and ultimately leading to severe dementia and inability to care for themselves. The cause of Alzheimer’s is not known but likely involves a combination of genetic, biochemical and environmental factors. Some genes have been identified as risk factors but monozygotic twins discordant for Alzheimer’s disease suggest other factors must contribute to development of the disease. Investigation on epigenetic marks including DNA methylation and post-translational modifications of histones have shown that the patterns of these modifications change with age in the human population. Though individuals show specific differences in epigenetic marks at the individual gene level, there is a consistent pattern of epigenetic changes at the genome scale across the population. Similar changes have been identified in patients with Alzheimer’s disease, though these occur at an earlier age compared to healthy individuals. The early cognitive impairment in Alzheimer’s disease can be mistaken for premature ageing correlating with the timing of epigenetic changes occurring at a younger age in individuals with Alzheimer’s. Such observations suggest that the epigenetic changes may contribute to disease pathology. Exactly how epigenetic modifications contribute to specific aspects of Alzheimer’s disease is the focus of many researcher groups across the world. A number of drugs are available that inhibit the enzymes that modify chromatin and change the epigenetic landscape of the genome. Therefore, an understanding of the role of chromatin modifications in Alzheimer’s could offer an opportunity for novel therapeutic strategies. Research using animal models of Alzheimer’s suggests that the epigenetic changes in Alzheimer’s disease may have a profound impact on cognition and underlie cognitive impairment while there is no clear evidence that they might contribute directly to neuronal loss.